Augmented Reality sebagai Media Pembelajaran Security Features Paspor pada Pendidikan Vokasi Keimigrasian - Sianipar, Passion Timothy Gerald (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning about passport security features in immigration vocational education is still dominated by conventional methods such as lectures and static media, which are less effective in presenting the technical details of security features. This limitation creates a gap between theory and students' analytical skills. This study aims to identify the weaknesses of conventional methods and develop Augmented Reality (AR)-based learning media using the Lean Product Development (LPD) framework. The learn phase maps student needs, the build phase produces AR prototypes in the form of 3D models of Indonesian, Swiss, and Canadian passports with key security features, while the measure phase evaluates effectiveness through limited trials. The results show that AR increases motivation, interactivity, and understanding of features that are difficult to observe directly. Thus, AR has the potential to be a learning innovation that can bridge the gap between theory and practice.